RELIGIUSITAS NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY (KAJIAN SOSIOLOGI SASTRA) - Dam Malhudji Asari (EDU-KATA, 2014)
This study aims to explain the values of religiosity in the Cinta Suci Zahrana novel. Data of this study is Cinta Suci Zahrana novel which created by Habiburrahman El Shirazy that published in May of 2011. This study uses form of primary data and secondary data. Collection data of this technique are implemented with the documentation, reading, collecting, and writing (BST). Instrument of this study are the researcher and pieces of the data corpus. This study uses a qualitative method using the theory of religiosity to know the religious values in the Cinta Suci Zahrana novel whichcreated by Habiburrahman El Shirazy. The results of this study as follows: the first, the values of faith which consist of : belief in the essential principal of faith, ridla 'with God, be afraid to God, and thanks to God for His abundant blessings. The second, the worship of mahdlah value consists of prayer and fasting. The third, the values of worship ghairu mahdlah consist of studying, prayer, alms, remember to Allah, ask forgiveness to Allah, and married. The fourth, the moral values to God consist of : belief that Allah is the only God in the world, pray fervently to God, expect the mercy of God, and good prejudiced to God. The Fifth, the moral values to others people consist of the morals of the family : be friendly, dutiful to parents, pray for parents, and take care to family members. And morals of society give mutual aid in good, friendship, remind others to do the truth, , keeping the promises, , establish the justice, give precedence to others interest, keep in unity, forgive others not be arrogant, take care to guests, calm in every situation, and always said the good thing. The Sixth, the moral values for the milieu are included care to the plants and kind to the animals.